Shoe Dryer Using Fuzzy Logic Controller with Internet of Things-Based Monitoring - Permata Dewata, Aqsal Renaldi; Widayaka, Parama Diptya; Rusimamto, Puput Wanarti; Baskoro, Farid (Universitas Bumigora, 2024)
Background: When the rainy season arrives, the main problem faced is the drying process of shoes due to uncertain weather. Moreover, drying the shoes directly under the sun can reduce the glue's durability and damage the shoes' material.Objective: This research aims to create an automatic shoe dryer that can be monitored online and uses fuzzy logic to maintain a stable temperature to maintain shoe durability.Methods: This research uses the fuzzy Mamdani method with ESP32 as a microcontroller to regulate the temperature stability of the shoe drying box.Results: Sneaker shoes were found to dry at 52% humidity and stable temperature at ± 410C within 82 minutes. Meanwhile, leather shoes dried at 62.9% humidity, and the temperature stabilized at ±350C within 20 minutes.Conclusion: The application of Mamdani fuzzy logic has an effect in stabilizing the temperature; if the drying box is tested without using a controller, the temperature will continue to increase, and the humidity will drop quickly, resulting in shoes not being completely dry.